Penerapan Pendekatan Supervisi Kolaboratif untuk Meningkatkan Kompetensi Profesional Guru Non PNS di MTs Negeri 1 Sintang - Nuriyansyah, Nuriyansyah (Al-DYAS, 2023)
The teaching and learning process is a reciprocal relationship between teachers and students in order to achieve learning objectives. A teacher has a very important role in delivering learning so that it is well received by students. In addition, teachers also play a role in shaping the attitudes, behaviors, and thought processes of students. In the learning process, the teacher becomes one of the learning resources so that they must have the ability to master the subject matter. In order to carry out their duties properly, teachers must have one dimension of competence in accordance with the Regulation of the Minister of National Education of the Republic of Indonesia Number 16 of 2007 concerning Standards of Academic Qualifications and Teacher Competencies, namely professional competence. The study used the School Action Research (PTS) method with the Kemmis and Mc. Taggart models which are development models from the Kurt Lewin model. The model used consists of 2 cycles, each cycle consists of four components, namely: planning, action, observation and reflection. This research begins with an initial reflection phase to conduct preliminary studies as a basis for formulating research problems. Furthermore, followed by planning, action, observation, and reflection The implementation of collaborative supervision can increase the professional competence of non-civil servant teachers in MTsN 1 Sintang by 18.19%. The average professional competence in cycle 2 was 88.64 with a good category.